Designing an Authentic Listening Assessment for Young Learners in Indonesian Primary Schools - Muamaroh; Nur Mufid; Mauly Halwat Hikmat (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2026)
Listening is a fundamental language skill that plays a crucial role in children’s language development and serves as the foundation for the acquisition of other language skills. However, listening assessment practices in English language teaching at Indonesian elementary schools are still predominantly dominated by traditional written tests, which inadequately represent students’ communicative listening abilities. This study aims to examine the design and implementation of authentic assessment for assessing listening skills in elementary English classrooms. Employing a descriptive qualitative approach, the study involved 30 students from Grades 4, 5, and 6 across five elementary schools in Central Java. The study was conducted in December during the first semester of the 2025/2026 academic year. Data were collected through classroom observations, semi-structured interviews with teachers, and the analysis of assessment rubrics and observation checklists. The data were analyzed using thematic analysis to identify patterns related to task design, validity, reliability, and feedback practices. The findings reveal that authentic listening tasks, such as following oral instructions, picture dictation, and classroom-based projects, enable students to demonstrate meaningful listening comprehension through actions and interactions. These tasks enhance student engagement, confidence, and motivation while providing richer evidence of listening competence for teachers. Nevertheless, several challenges were identified, including time constraints, large class sizes, and issues related to assessment consistency. Further findings indicate that the use of simple rubrics and timely, supportive feedback plays a critical role in improving the reliability of performance-based listening assessment. Overall, authentic listening assessment emerges as an effective and relevant alternative to complement traditional assessment practices in elementary English education.